The Implementation of Sharia in Aceh (Pelaksanaan Syariat Islam di Aceh) - Misran Misran (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2012)
Implementation of sharia in Aceh is identified as the historical-sociological value. This provision is developed based on the reaction of the Acehnese people who expect the rules of sharia are born through the Qanun. Therefore, imposition of Islamic sharia and how well are they enforced, seems adapted to the prevailing customs and traditions, as proof with the Qanun 9/2009 on the implementation of indigenous life and Qanun 10 of the customary institutions ratified on December 30, 2008, which previously was in the form of local government 7/2003. Then how are the views and the response to the enactment and implementation of sharia in Aceh. This course requires an effort to consider the legal systems that do not experience gaps in supporting the establishment of sharia in Aceh.